DOI: 10.23889/suthesis.60416
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modified Polymers and Nanoparticles for Enhanced Oil Recovery (EOR) Application

Abstract: The study to improve hydrocarbon recovery has attracted a great deal of research at-tention in many directions such as using chemical treatment or CO2 injection, and hydrocarbon fracking. The research trials are based on either studying a new approach to recovery or investigating the effect of injection agent treatments. Nanoparticles are a chemical addition that has promise in changing the reservoir properties through dif-ferent mechanisms such as: wettability alteration, reduce oil/water mobility, increase v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 198 publications
0
3
0
Order By: Relevance
“…Stability is a key parameter which must be considered for application of foams (Bai et al 2010;Guo and Aryana 2016;Ibrahim et al 2017;Risal et al 2019;Yang et al 2017). Some factors like reservoir condition (e.g., reservoir temperature, pressure, oil saturation and composition, brine saturation and composition), foaming agent and its concentration and type of gas affect foam stability (Almubarak et al 2020;Grigg et al 2004). Thus, for EOR purposes, the longer the lifetime of the lamella, the greater the stability of the foam will be achieved (Zhu et al 2004).…”
Section: Hybrid Of Nanoparticles and Foammentioning
confidence: 99%
See 2 more Smart Citations
“…Stability is a key parameter which must be considered for application of foams (Bai et al 2010;Guo and Aryana 2016;Ibrahim et al 2017;Risal et al 2019;Yang et al 2017). Some factors like reservoir condition (e.g., reservoir temperature, pressure, oil saturation and composition, brine saturation and composition), foaming agent and its concentration and type of gas affect foam stability (Almubarak et al 2020;Grigg et al 2004). Thus, for EOR purposes, the longer the lifetime of the lamella, the greater the stability of the foam will be achieved (Zhu et al 2004).…”
Section: Hybrid Of Nanoparticles and Foammentioning
confidence: 99%
“…Some surfactants and polymers could be used as foam stabilizers (Yekeen et al 2018). Due to sensitivity of surfactants and polymers to high salinity and temperature (Babamahmoudi and Riahi 2018;Farzaneh and Sohrabi 2015;Ko and Huh 2019;Kutay and Schramm 2004;Lee et al 2015;Singh and Mohanty 2017;Yekeen et al 2017), recently novel methods such as combination of foams and nanoparticles (Almubarak et al 2020) have been suggested as a solution to improve the stability of foams during flooding. Studies have shown that the use of nanoparticles as foam stabilizer leads to beneficial effects (X.…”
Section: Hybrid Of Nanoparticles and Foammentioning
confidence: 99%
See 1 more Smart Citation